Actividades Experimentales con Tecnologías en Escenarios de Modelización Matemática - Villarreal, Mónica E. [UNESP]; Mina, María (UNESP - Universidade Estadual Paulista, Pró-Reitoria de Pesquisa Programa de Pós-Graduação em Educação Matemática, 2020)
This article analyses the realization of experimental activities carried out by groups of second-year students from a secondary school in Córdoba (Argentina), within the framework of open modelling projects with the free use of technologies. The students developed these projects in modeling scenarios created in their mathematics classes. Our research seeks to investigate: 1) the learning of students participating in active mathematical modeling scenarios with experimental activities and digital technologies and, 2) the role that digital technologies play in modeling processes that involve experimental activities. In theoretical terms, the perspective of situated learning and the epistemological vision embedded in the humans-with-media construct are adopted. Learning is evidenced by the participation of students in different phases of mathematical modeling processes developed in local communities of practice in the educational context.The digital technologies most used by the students were their cell phones and cameras, to record experiments and take measurements, and mathematical software to represent graphs and communicate results. These uses were related to the experimentation and resolution phases. The in-depth analysis of a particular project shows the potential and creative use of various digital technologies in these phases. It is important to note that the study provides an example that responds to curricular recommendations around the inclusion of modeling and the use of technologies in mathematics classes. Finally, we reflect on the importance, for teacher education, of living experiences such as the one reported in this study.

Este artículo analiza el desarrollo de actividades experimentales realizadas por grupos de estudiantes de segundo año, de una escuela secundaria en la ciudad de Córdoba (Argentina), en el marco de proyectos de modelización abiertos, acompañados por el libre uso de tecnologías. Los estudiantes desarrollaron estos proyectos en escenarios de modelización creados en sus clases de matemática. Nuestra investigación busca indagar acerca de: 1) el aprendizajede estudiantes que participan en escenarios de modelización matemática activa con actividades experimentales y tecnologías digitales y 2) el papel que desempeñan las tecnologías digitales en procesos de modelización que involucran actividades experimentales. En términos teóricos, se adopta la perspectiva del aprendizaje situado y la visión epistemológica involucradaen el constructo humanos-con-medios.Los aprendizajes se evidencian en la participación de los estudiantes en distintas fases de procesos de modelización matemática, desarrollados en comunidades locales de práctica en contexto educativo. Las tecnologías digitales más empleadas por los estudiantes fueron celulares y cámaras fotográficas, para registrar experimentos y tomar mediciones, y software matemático para representar gráficos y comunicar resultados. Estos usos estuvieron relacionados con las fases de experimentación y resolución. El análisis en profundidad de un proyecto particular muestra la potencialidad y el uso creativo de diversas tecnologías digitales en estas fases. Se destaca que el estudio brinda un ejemplo que responde a recomendaciones curriculares en torno a la inclusión de la modelización y el uso de tecnologías en clases de matemática. Finalmente, se reflexiona acerca de la importancia, para la formación de profesores, de vivenciar experiencias como la aquí reportada.
Experimental Activities with Technologies in Mathematical Modeling Scenarios
Keywords: Mathematical modeling; Digital Technologies; Experimental activities; Situated learning; Secondary school